Laboratory Response to 2014 Ebola Virus Outbreak in Mali - Diarra, Bassirou (J Infect Dis, 2016)
Aware of the rapid spread of Ebola virus (EBOV) during the current West African epidemic, Mali took several proactive steps to rapidly identify cases within its borders. Under the Mali International Center for Excellence in Research program, a collaboration between the National Institute of Allergy and Infectious Diseases and the Malian Ministry of Higher Education and Scientific Research established a national EBOV diagnostic site at the University of Sciences, Techniques and Technologies of Bamako in the SEREFO Laboratory. Two separate introductions of EBOV occurred in Mali from neighboring Guinea, but both chains of transmission were quickly halted, and Mali was declared “Ebola free” on 18 January 2015 and has remained so since. The SEREFO Laboratory was instrumental in the success of Mali's Ebola response by providing timely and accurate diagnostics. As of today, the SEREFO Laboratory has tested 103 samples from 88 suspected cases, 10 of which were EBOV positive, since the Ebola diagnostics unit started in April 2014. The establishment of Ebola diagnostics in the SEREFO Laboratory, safety precautions, and diagnostics are described.